Women Frame in Media Discourse - Ichsan Adil Prayogi (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This research is motivated by high public attention in the case of online prostitution Vina Garut, which is reporting about her the case brings up gender discrimination, and the media that actively contribute to these cases is suara.com. In this study, the authors pick nine news the period 15 August to 21 September 2019, which are then analyzed using Sara Mills's critical discourse analysis. From the results of the analysis, Vina is a woman who is at the same time is displayed as a negative character in this case. Apart from that, Vina is also positioned as an objectified party. This is seen in the way the media features news that highlighted gender discrimination. Researchers see that patriarchal discourse in Indonesia still positions women as people who have high news values but are also vulnerable to being positioned unevenly. Researchers also see that the media of the object of this article's research has tried to choose diction and arrange sentences in a balanced manner. But patriarchal ideological discourse is still seen in several narratives and readings of the production and consumption of public discourse in news portals in particular and discourse in public in general.